Extending beyond traditional forage: potential nutritional benefits of native plants in extreme arid insular regions - Pérez-Reverón, Raquel; Perdomo-González, Adolfo; de la Roza-Delgado, Begoña; Rodríguez, Covadonga; Pérez-Pérez, José A.; Díaz-Peña, Francisco J. (Frontiers in Plant Science, 2024)
The scarcity, unstable nutritional quality and environmental cost of imported forages in arid insular regions like Fuerteventura in the Canary Islands (Spain) need exploring sustainable local alternatives. This study evaluated the nutritional quality of twelve native and endemic plant species categorized into legumes, grasses, and a mixed group, cultivated under controlled conditions. The bromatological profiles, focusing on fiber, protein, lipids, and minerals, showed significant differences among plants in key parameters of forage quality: neutral detergent fiber (NDF; 24.2–71.3%), acid detergent fiber (ADF; 9.0–40.5%), acid detergent lignin (ADL; 2.0–15.8%), crude protein (CP; 6.1–20.9%), total lipids (TL; 1.5–6.3%), ash content (25.4–88.6%), enzymatic organic matter digestibility (EOMD; 5.9–10.9 MJ/kg), metabolizable energy (ME; 5.9–10.9 MJ/kg), and relative feed value (RFV; 74.8–317.9). Among lipids, all species had a high proportion of polyunsaturated fatty acids (PUFA; 34.7–63.1% of total fatty acids), mainly α-linolenic acid (ALA; 18:3 n-3; 24.8–54.4%) and linoleic acid (LA; 18:2 n-6; 6.4–25.0%). Other beneficial lipid molecules for animal health such as γ-linolenic acid (GLA; 18:3 n-6), stearidonic acid (SDA; 18:4n-3) and phytosterols (PTS) were detected in specific species. Mineral composition analysis revealed that only Ca, Na, Fe and Cu levels were near or above the established maximum tolerable levels (MTLs) in some species. According to literature, most of the species had a similar or slightly lower nutritional value compared to conventional forages such as alfalfa. Thus, the evaluated native species pool could serve as alternative feed for ruminants during forage shortages, suggesting their combined use to improve livestock health and product quality. This research emphasizes the untapped potential of native plant biodiversity to enhance sustainable agro-livestock practices in arid regions, supporting livestock nutrition and conserving unique botanical heritage.